Financial distress, incentives and the value of corporate insurance - Luc L. Grillet (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
Positive contracting costs (imperfect marketability), the impos-sibility of complete spanning of State spaces and other market imperfections explain the relevance of the corporate buying of property and liability insurance. For a corporation with diffuse ownership, risk aversion is irrelevant, since investors can diversify unsystematic (insurable) risks. Corporate insurance purchasing may enhance the market value of the firm via taxes, regulatory costs, contracting costs or the impact of financial policy on the firm's investment decision. Particularly in the case where financial distress depresses the market value of the firm, insurance hedging appears to be valuable. The magnitude of the insurance benefit is hypothesized to be positively correla-ted with the ratio of the firm's implicit over explicit Claims.
Keywords: 330